MEDIA LITERACY FOR TEACHER: PREVENTING EXTRIMISM AND RADICALIZATION IN SCHOOLS - Bono Setyo; Witriani Witriani; Alimatul Qibtiah (Profetik: Jurnal Komunikasi, 2020)
One of the biggest global challenges of this era is the rise in extreme violent behavior (extremism) and radicalization among the younger generation, especially high school students. The most prominent extremism and radicalism today is religion-based, which is generally driven by the exclusivity of ideological, political, racial or ethnic groups. We cannot deny the fact that the group most vulnerable to extremism and radicalism is a group of middle school students, given their age in the search for identity and sometimes burning by excess energy which if not channeled into positive channels can actually increase the tendency of extremism and radicalization. One of the biggest determinants of extremist tendencies and radicalization towards students is the teacher and the school environment. Compared with parents, teachers have more frequency and intensity of interaction with them, so teachers are expected to be able to teach and give examples of character values such as attitude of respect, tolerance, mutual respect for differences, honesty, and others. Therefore the inculcation of values is characterized by preventing extremism and radicalization and must be preceded by efforts to increase teacher understanding through media literacy.